2018
DOI: 10.1111/ajco.12840
|View full text |Cite
|
Sign up to set email alerts
|

Risk of febrile neutropenia and early treatment cessation in men receiving standard and dose‐reduced 3‐weekly docetaxel for metastatic castration‐resistant prostate cancer

Abstract: LD docetaxel for mCRPC did not mitigate the risk of FN or ETC due to toxicity. Dose reduction may result in poorer PSA response and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, in our results, similar predictors were not significant (except for ECOG PS). An Australian study of 166 mCRPC patients treated with docetaxel also found no significant association between patient baseline characteristics and FN 24 . In line with the American Society of Clinical Oncology guidelines, 25 a retrospective study of 1241 lymphoma patients receiving chemotherapy found no increased risk of FN in overweight patients 26 .…”
Section: Discussionmentioning
confidence: 91%
“…However, in our results, similar predictors were not significant (except for ECOG PS). An Australian study of 166 mCRPC patients treated with docetaxel also found no significant association between patient baseline characteristics and FN 24 . In line with the American Society of Clinical Oncology guidelines, 25 a retrospective study of 1241 lymphoma patients receiving chemotherapy found no increased risk of FN in overweight patients 26 .…”
Section: Discussionmentioning
confidence: 91%